Differential vulnerability of neuronal subpopulations of the subiculum in a mouse model for mesial temporal lobe epilepsy - Franz, Julia; Barheier, Nicole; Wilms, Henrike; Tulke, Susanne; Haas, Carola A.; Häussler, Ute (Frontiers in Cellular Neuroscience, 2023)
Selective loss of inhibitory interneurons (INs) that promotes a shift toward an excitatory predominance may have a critical impact on the generation of epileptic activity. While research on mesial temporal lobe epilepsy (MTLE) has mostly focused on hippocampal changes, including IN loss, the subiculum as the major output region of the hippocampal formation has received less attention. The subiculum has been shown to occupy a key position in the epileptic network, but data on cellular alterations are controversial. Using the intrahippocampal kainate (KA) mouse model for MTLE, which recapitulates main features of human MTLE such as unilateral hippocampal sclerosis and granule cell dispersion, we identified cell loss in the subiculum and quantified changes in specific IN subpopulations along its dorso-ventral axis. We performed intrahippocampal recordings, FluoroJade C-staining for degenerating neurons shortly after status epilepticus (SE), fluorescence in situ hybridization for glutamic acid decarboxylase (Gad) 67 mRNA and immunohistochemistry for neuronal nuclei (NeuN), parvalbumin (PV), calretinin (CR) and neuropeptide Y (NPY) at 21 days after KA. We observed remarkable cell loss in the ipsilateral subiculum shortly after SE, reflected in lowered density of NeuN+ cells in the chronic stage when epileptic activity occurred in the subiculum concomitantly with the hippocampus. In addition, we show a position-dependent reduction of Gad67-expressing INs by ~50% (along the dorso-ventral as well as transverse axis of the subiculum). This particularly affected the PV- and to a lesser extent CR-expressing INs. The density of NPY-positive neurons was increased, but double-labeling for Gad67 mRNA expression revealed that an upregulation or de novo expression of NPY in non-GABAergic cells with a concomitant reduction of NPY-positive INs underlies this observation. Our data suggest a position- and cell type-specific vulnerability of subicular INs in MTLE, which might contribute to hyperexcitability of the subiculum, reflected in epileptic activity.